Turnout in the Municipal Elections of March 2020 and Excess Mortality during the COVID-19 Epidemic in France - Simone Bertoli; Lucas Guichard; Francesca Marchetta (Institute of Labor Economics (IZA), 2020)
We analyze the consequences of the decision of French government to maintain the first round of the municipal elections on March 15, 2020 on local excess mortality in the following weeks. We exploit heterogeneity across municipalities in voter turnout, which we instrument using a measure of the intensity of local competition. The results reveal that a higher turnout was associated with a significantly higher death counts for the elderly population in the five weeks after the elections. If the historically low turnout in 2020 had been at its 2014 level, the number of deaths would have been 21.8 percent higher than the one that was recorded. More than three quarters of these additional deaths would have occurred among the individuals aged 80 and above.
Keywords: J11; D72; 330; COVID-19; excess mortality; voter turnout; intensity of electoral competition; municipal-level data